Analisi Dampak Perilaku Minum Tuak di Desa Kuta Dame, Kec. Pakpak Bharat (International Forum of Researchers and Lecturers, 2024)
Kuta Dame Village is a fairly crowded village. This village is where I researched How the Impact of Tuak Drinking Behavior. The research method used is a qualitative approach by conducting interviews with business owners and literature studies by obtaining information from journals, books as a source of Tuak literature derived from palm trees. Palm trees are versatile plants that from the stem to the leaves can be used and can also be sold. Palm sap can be used as an alcoholic beverage, although it does not have a high alcohol content as in general. There are two types of palm drink from the palm tree, commonly called sap, namely sweet and bitter. For the sweet ones, there is no such thing as raru so that it can be managed again into palm sugar. And there is also sweet wine added with raru so that it has a bitter taste and adds alcohol content to the drink and can also preserve the drink. Tuak shops are always everywhere, both in villages, cities and even parties that sell them. Selling wine is an easy thing to do at any time, Income always increases so they keep doing that business. Requesters for wine are numerous. Fans of wine are more men, they will often go out to drink and they think that drinking wine can relieve stress, thoughts. Tuak can be used as opium because the taste of alcohol is right and the price is also different from the price of alcohol in general. However, wine is not good if consumed excessively and continues to cloud because it is not good for health. However, the presence of wine can cause poisoning, weight gain, high blood pressure, impaired liver function, weakened immune system, heart disorders, nerve damage, impaired reproductive (sexual) function, mental health disorders and decreased intelligence